Seed germination of a rare neotropical canopy tree dormancy and the effects of abiotic factors - Ramos,Flavio Nunes (2010)
The purpose of this study was to examine if germination is a critical phase on Enterolobium glaziovii regeneration. Hence, the germinative response of E. glaziovii seeds was investigated in relation to some of the main environmental factors (temperature, light and water stress) to which its seeds are subjected in the forest, as well as its dormancy and the longevity of its burial seeds. According to our results, its seeds may be regarded as photoblastic neutral. They do not need alternating temperatures to germinate and can germinate under a broad range of water stress. However, only about 10% of E. glaziovii seeds remain viable after one year. In other words, the annual fruiting, instead seed longevity, seems to maintain the long-term seed availability of this species. Consequently, the seed longevity could be a critical phase of E. glaziovii germination.